THE ROLE OF PRINCIPAL IN CURRICULUM AND LEARNING MANAGEMENT - Bening Sri Palupi; Ervina Esti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aims to describe the role of school principals in curriculum and learning management at SDN Manahan Banjasarsari District Surakarta City. The formulation of this research is how the role of school principals in curriculum and learning management, to obtain the data used interview techniques and filling questionnaires. The validity of the data is done by means of source triangulation, ie analyzing the results of interviews and questionnaires based on the theory used and relevant research studies as a comparison material. Data analysis technique used is interactive analysis. The results can be concluded that the role of school principals in curriculum management and learning in SDN Manahan is more likely to play a role as a curriculum tool maker. This can be seen from the headmaster not only providing socialization of the 2013 curriculum to teachers and school committees, but also providing socialization to parents.